2010
DOI: 10.1152/ajpheart.00400.2009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of angiotensin-(1–7) on the nerve stimulation-induced release of norepinephrine and neuropeptide Y from the mesenteric arterial bed

Abstract: Neuropeptide Y (NPY) is a cotransmitter with norepinephrine (NE) and ATP in sympathetic nerves. There is evidence for increased activity of the sympathetic nervous system and the renin-angiotensin system (RAS), as well as a role for NPY in the development of hypertension in experimental animal models and in humans. Angiotensin II (ANG II) is known to facilitate sympathetic neurotransmission, an effect greater in spontaneously hypertensive rats (SHR) than normotensive Wistar-Kyoto (WKY) rats. A newly discovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 54 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…When all HUT(ϩ) subgroups were analyzed collectively, an increase in hormone secretion from the supine position to HUT included AVP, NE, Epi, renin, and ANG II. Although ANG-(1-7) has been reported to influence AVP and NE release and baroreflex function in animal studies (7,17,44,57), there were no differences in ANG-(1-7) between groups. A negative relationship was observed between ANG-(1-7) and NE, consistent with evidence of a neuromodulatory action of ANG-(1-7) on the release of NE (7, 17, 48, 57).…”
Section: Discussionmentioning
confidence: 73%
“…When all HUT(ϩ) subgroups were analyzed collectively, an increase in hormone secretion from the supine position to HUT included AVP, NE, Epi, renin, and ANG II. Although ANG-(1-7) has been reported to influence AVP and NE release and baroreflex function in animal studies (7,17,44,57), there were no differences in ANG-(1-7) between groups. A negative relationship was observed between ANG-(1-7) and NE, consistent with evidence of a neuromodulatory action of ANG-(1-7) on the release of NE (7, 17, 48, 57).…”
Section: Discussionmentioning
confidence: 73%
“…This increase in O 2 − will decrease NO availability and further augment norepinephrine levels in the neurovascular junction that will then blunt NPY release via negative feedback mechanisms. A further example is the observation that, in addition to direct pre-junctional inhibitory effects on norepinephrine and NPY overflow, the angiotensin metabolite, Ang 1–7 decreases norepinephrine overflow from the mesenteric bed in a NOS dependent manner (Byku et al , 2010). …”
Section: The Role Of No In Differential Modulation Of Sympathetic Neumentioning
confidence: 99%
“…Findings involving the application of A-779 to evaluate Ang-(1–7) actions appear to confirm the involvement of the mas-R (Santos et al, 1994). Using this antagonist, studies have reported that A-779 prevents the inhibitory actions of Ang-(1–7) on nerve stimulation-mediated release of norepinephrine and neuropeptide Y (Byku et al, 2010), myocardial contractility (Castro-Chaves et al, 2009), and stimulation of cardiac Akt phosphorylation and Ang II-stimulated ERK1/2 and Rho kinase phosphorylation (Giani et al, 2008). The use of mice with genetic deletion of the mas-R has affirmed conclusions derived from pharmacological blockade of Ang-(1–7) (Santos et al, 2003, 2006).…”
Section: The Ace2/ang-(1–7)/mas Axismentioning
confidence: 99%